2009
DOI: 10.1111/j.1365-294x.2009.04133.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow of Acanthaster planci (L.) in relation to ocean currents revealed by microsatellite analysis

Abstract: Population outbreaks of the coral-eating starfish, Acanthaster planci, are hypothesized to spread to many localities in the Indo-Pacific Ocean through dispersal of planktonic larvae. To elucidate the gene flow of A. planci across the Indo-Pacific in relation to ocean currents and to test the larval dispersal hypothesis, the genetic structure among 23 samples over the Indo-Pacific was analysed using seven highly polymorphic microsatellite loci. The F-statistics and genetic admixture analysis detected geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 88 publications
3
113
0
Order By: Relevance
“…Hence, our data strongly suggest that isolation by large distances allows for genetic divergence, even in high-dispersal organisms like planktonic diatoms. This is in line with other marine organisms, where similar patterns of significant IBD were observed from regional to global scales (23,(50)(51)(52).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Hence, our data strongly suggest that isolation by large distances allows for genetic divergence, even in high-dispersal organisms like planktonic diatoms. This is in line with other marine organisms, where similar patterns of significant IBD were observed from regional to global scales (23,(50)(51)(52).…”
Section: Resultssupporting
confidence: 72%
“…Flow patterns of tidal or oceanic currents may also contribute to the genetic isolation among global populations by hindering dispersal (22,23,28,58,59). For example, there were no significant F ST values between populations from the North Sea and a connected Danish inland fjord, yet populations from the Irish Sea and the adjacent North Sea showed significant differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly significant F ST value for all ten microsatellite loci between the IO and WP populations (combined Phuket-Thailand, SEA, Australia), reciprocal monophyly in mitochondrial lineages, the clear separation of nuclear alleles and the population assignment findings strongly indicate the lack of contemporary gene flow between these populations despite the absence of current geographic/physical barriers for dispersal and gene flow. This lack of contemporary gene flow among IO and WP populations has also been demonstrated in many other reef-associated fauna (Yasuda et al, 2009;Leray et al, 2010). The habitat preference of shallow coastlines and the lack of larval stages that allow long distance dispersal may prevent sea snakes from crossing deeper seas and population connectivity reducing gene flow.…”
Section: Past and Present Barriers To Dispersal And Gene Flow Betweenmentioning
confidence: 99%
“…E-mail: wbongkot@gmail.com This lack of connectivity can be seen in the genetic differentiation of many organisms, for example, coral (Clifton, 1997;Knittweis et al, 2009), macroalgae (Maggs & Callow, 2002), crustaceans (de Bruyn et al, 2005;Obst et al, 2012) and plants (Liao et al, 2009). Moreover, molecular genetic analyses of anemone fish (Timm & Kochzius, 2008), seastars (Yasuda et al, 2009) and coral (Knittweis et al, 2009) have found a clear genetic break between Indian and Pacific Ocean populations, which has been attributed to the ocean current patterns in the region.…”
Section: Introductionmentioning
confidence: 99%